1979
DOI: 10.1111/j.1365-2125.1979.tb04787.x
|View full text |Cite
|
Sign up to set email alerts
|

Labetalol infusion in acute myocardial infarction with systemic hypertension.

Abstract: 1 Fifteen patients with suspected acute myocardial infarction and systemic BP of greater than 160/110 mmHg were treated with an incremental infusion of labetalol. 2 Systemic BPs were safely and effectively lowered to less than 130 mmHg systolic or 90 mmHg diastolic in all patients. 3 Heart rate, mean pulmonary artery wedge pressure cardiac index and stroke work index were significantly reduced. 4 The dose of labetalol varied from 30 mg-440 mg and was significantly higher (mean 295 mg) in those patients with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…However, at high levels of exercise there is some reduction in cardiac output (Edwards & Raftery, 1976). Cardiac output is also reduced at rest in patients with acute myocardial infarction, although this is predominantly related to a reduction in heart rate (Marx et al, 1979). Long-term continuous oral administration to hypertensive patients has confirmed the original findings (LundJohanssen, 1979;Koch, 1979).…”
supporting
confidence: 69%
See 3 more Smart Citations
“…However, at high levels of exercise there is some reduction in cardiac output (Edwards & Raftery, 1976). Cardiac output is also reduced at rest in patients with acute myocardial infarction, although this is predominantly related to a reduction in heart rate (Marx et al, 1979). Long-term continuous oral administration to hypertensive patients has confirmed the original findings (LundJohanssen, 1979;Koch, 1979).…”
supporting
confidence: 69%
“…We have seen one hypertensive patient develop subjective symptoms and objective signs of airways obstruction in labetalol that was reversed on dosage reduction without loss of BP control . The multicentre study reported two cases of heart failure in the study and the drug is probably best avoided in patients crucially dependent on their sympathetic drive to maintain cardiac output as suggested by the reduction in cardiac output seen after myocardial infarction (Marx & Reid, 1979).…”
Section: Side-effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…After continuous oral administration to patients, small reductions in resting heart rate are usually found (Lund-Johansen, 1979), although individual changes are influenced by the degree of resting sympathetic drive. Marked reductions in resting heart rate after labetalol may follow intravenous administration Marx & Reid, 1979).…”
Section: Clinical Pharmacology and Haemodynamicsmentioning
confidence: 99%